The idioms introduced in the Market Leader course books = Thành ngữ sử dụng trong sách giáo trình Market Leader - Nguyễn, Hương Thảo (2021)
Idiom is an important part of communication. However, sometimes idioms cause trouble because the native speakers of English do not self-recognize that the expressions - the idioms - they are using are special and unfamiliar to the nonnative speakers. For this reason, it is extremely important for students to learn to hear, and understand the idioms in natural contexts, specially the business contexts. Market Leader series are a useful source of idioms for students. In order to raise the understanding of idioms and to build up the habit of using idioms, the research study the idioms in business uses in the Market Leader books (Intermediate and Upper Intermediate) written by David Cotton, David Falvey, Simon Ken and published by Pearson Longman in 2006. In the research, the types of idioms commonly used in the business contexts, and in which business contexts idioms are used the most are investigated. The research also looks at how the double major students at the Faculty of English Language Teacher Education are learning idioms in the Market Leader course books by using a survey questionnaire. Carried out in the form of a case study of idioms in use and incorporated with a survey questionnaire, the research concludes that all the types of idioms are used in the business contexts and idioms are used at higher density in business conversations than in economics and business text formats (news and articles). Another important finding is that the double major students at the Faculty of English Teacher Education are quite aware of the importance of idioms in business uses and they are applying different techniques in learning idioms.